Strategi Pembelajaran Pendidikan Agama Islam dalam Perspektif Teori Belajar Behaviorisme Thorndike, Pavlov, dan Skinner - Ikhlas, Nur; Afandi, Muslim; Subhan, Mhd. (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to examine the application of behaviorist learning theories in Islamic Religious Education (PAI) through the perspectives of Edward L. Thorndike, Ivan Pavlov, and B.F. Skinner. The background of this research is the need for effective strategies in shaping students’ religious behavior in a structured and observable manner. Using a qualitative descriptive approach through library research, this study analyzes how key behaviorist principles—stimulus-response (Thorndike), classical conditioning (Pavlov), and operant conditioning with reinforcement (Skinner)—can be integrated into PAI learning strategies. The findings reveal that Islamic concepts such as targhib (positive motivation) and tarhib (warning) reflect classical conditioning mechanisms, while the use of rewards and punishments aligns with operant reinforcement. These approaches prove effective in developing students’ religious habits, discipline, and positive attitudes through repeated and consistent learning processes. The study concludes that behaviorist learning theory offers a strong pedagogical foundation for PAI instruction focused on behavior formation. Its practical implications suggest that educators can enhance religious character education by systematically applying behaviorist principles within the Islamic context.